ANALYSIS OF ELASTIC CONSTANTS OF HOLLOW GLASS MICROSPHERE / EPOXY SYNTACTIC FOAM REINFORCED BY GLASS FIBER - YU Wei; LIU Shuang; LI HuiJian; LIANG Xi (Jixie qiangdu)
The mechanical properties of hollow glass microsphere / epoxy syntactic foam can be reinforced by adding glass fiber. Two numerical simulation models have been established with two different hollow glass microsphere and glass fiber arrangements. The change rules between elastic constants and volume fraction,relative wall thickness and stress distribution rules are studied. It is found that the elastic modulus of composites increases with the increase of glass microsphere relative wall thickness,while the changing rules with volume fraction show different patterns in different relative wall thickness. Poisson’s ratio decreases with volume fraction increase,but it increases before then reduce with the relative wall thickness. The elastic modulus prediction formula along the fiber axial was proposed according to Voigt model and mix law. The prediction results are close to numerical simulation results when the relative wall thickness less than 0. 2.